2015 ACC/AHA Focused Update of Secondary Prevention Lipid Performance Measures: A Report of the American College of Cardiology/American Heart Association Task Force on Performance Measures. (January 2016) - Drozda, Joseph P.; Ferguson, T. Bruce; Jneid, Hani; Krumholz, Harlan M.; Nallamothu, Brahmajee K.; Olin, Jeffrey W.; Ting, Henry H.; Heidenreich, Paul A.; Albert, Nancy M.; Chan, Paul S.; Curtis, Lesley H.; Ferguson, T. Bruce; et al.
Abstract : Supplemental Digital Content is available in the text.